Evaluating the performance of inspectors general offices in reducing corruption According to global indicators(Field research comparative) - الكبيسي, صلاح الدين عواد; متعب, طلال (Journal of Economics and Administrative Sciences, 2017)
Abstract        This research aims to evaluate the application of the inspectors general of global indicators offices according to the axles (leadership, strategy and planning, employees, partners and resources, process management) and through the assumption main research which states that (there is an application for global indicators to evaluate performance in the offices of the ministries under study) which are subdivided into five sub-hypotheses according to the classification and division of the five axes of the checklist.The researchers have taken refuge in the process of assessing the performance of the check list which included global indicators, which are certified by the European Union in assessing organizations as Arad, the researchers use a global indicator to show the aspects of the real weaknesses and their suitability in the application of national organizations, and selected the inspectors general of ministries and offices (Education and Culture and health) subject to the application of the practical side, which was based on direct field study was the analysis of the final results of this hypothesis using statistical methods (Mean unlikely, central premise, the standard deviation, the test Altaia "t-test"  Contrast "ANOVA test" analysis test ). In light of the theoretical and practical study, the researchers reached a set of results, notably.shows that there are weak and inadequate in the application of global indicators in the surveyed offices, as an indicator of staff for Strategic and index layout and index partners and resources of the three offices (education, culture and health) and transaction management for office Index (education and health).Show that there are significant differences between the surveyed in terms of the application of global indicators offices, it was the highest value for the Office of the Inspector General of the Ministry of Culture and then followed by the Office of the Inspector General of the Ministry of Health and Ministry of Education and the Office of differences.